Hybrid detection in lychee (Litchee chinensis Sonn.) cultivars using HAT-RAPD markers - R. Chundet (2018)
In this paper we present a method to detect hybrids obtained from open-pollinated seeds in lychee cultivars (Litchi chinensis Sonn.) using the high annealing temperature randomly amplified polymorphic DNA (HAT-RAPD) methodology. A series of 10 arbitrary random primers were used to amplify polymorphic DNA bands ranging from 200 to 1,700 bp. These bands were tracked from parent to hybrid offspring for crosses of four economically important lychee varieties (Chacrapat, Kimjeng, Hong Huey and O-Hia) and both gender and variety specific band transmission rates were assessed. Irrespective of lychee variety, all hybrids showed a significant loss of parental bands with the largest losses occurring between the male parent and the offspring. Variety-specific bands were characterized for each lychee variety and hybrid band transmission rates were determined such that hybrids could be detected to any level of desired significance given enough initial banding data. This molecular marker technique provides a clear and compelling way to ascertain hybrid status of new plants without having to wait the six to seven years for the plants to mature.